Medical misinformation in the digital age: current challenges and future directions - Lees, Elen Mai (Social Determinants of Health, 2024)
Medical misinformation is a complex issue influenced heavily by the concept of health literacy levels and is defined as the claim of health-related fact(s) that does not align with evidence-based scientific consensus. Left unchallenged, it could have devastating outcomes for public health, and may present significant challenges for the implementation of future health prevention and promotion interventions. At present, Ofcom estimates that 40% of adults do not currently possess the necessary digital literacy skills to critically assess online content, and studies have found a positive correlation between the use of social media as an information source and COVID-19 conspiracy beliefs. Additional studies have also found evidence to suggest that vaccine hesitancy is linked with lower levels of overall health literacy. In conclusion, medical misinformation has the capacity to cause undoubted harm to public health if left unchallenged, particularly in the employment of health prevention and promotion interventions. Policy makers should consider the need for legislation combating the dissemination of medical misinformation, per Mamak’s argument for the criminalization of [online] medical fake news. Authors of scientific research should, in good faith, heed the advice of Bergstrom’s “Eight rules to combat medical misinformation” to aid in mitigating the potential for their work to be misrepresented or misinterpreted in the popular media.